The Passage Regimes of the Kerch Strait—To Each Their Own?. (2nd January 2021) - Lott, Alexander
Abstract: This study explores the passage regimes of the Kerch Strait and its adjacent maritime areas in the context of current arbitration proceedings between Ukraine and the Russian Federation. It ascertains that conflicting sovereignty claims over Crimea might lead to strait states and user states alike retaining their different approaches to the passage regime of the Kerch Strait. Thus, the regimes of transit passage and authorization-based passage might simultaneously be applied to the Kerch Strait under the domestic laws of the strait states, law of the sea, and general international law, particularly the obligation of nonrecognition. The law of the sea allows the reconciliation of such conflicting approaches and ensures legal certainty in the shipping lanes of the Kerch Strait if the coastal states agree on and respect a sui generis passage regime.